Topological Surface States in a Gyroid Acoustic Crystal. Issue 6 (16th December 2022) - Guo, Yuning; Rosa, Matheus I. N.; Ruzzene, Massimo
Abstract: The acoustic properties of an acoustic crystal consisting of acoustic channels designed according to the gyroid minimal surface embedded in a 3D rigid material are investigated. The resulting gyroid acoustic crystal is characterized by a spin‐1 Weyl and a charge‐2 Dirac degenerate points that are enforced by its nonsymmorphic symmetry. The gyroid geometry and its symmetries produce multi‐fold topological degeneracies that occur naturally without the need for ad hoc geometry designs. The non‐trivial topology of the acoustic dispersion produces chiral surface states with open arcs, which manifest themselves as waves whose propagation is highly directional and remains confined to the surfaces of a 3D material. Experiments on an additively manufactured sample validate the predictions of surface arc states and produce negative refraction of waves at the interface between adjoining surfaces. The topological surface states in a gyroid acoustic crystal shed light on nontrivial bulk and edge physics in symmetry‐based compact continuum materials, whose capabilities augment those observed in ad hoc designs. The continuous shape design of the considered acoustic channels and the ensuing anomalous acoustic performance suggest this class of phononic materials with semimetal‐like topology as effective building blocks for acoustic liners and load‐carrying structural components with sound proofing functionality. Abstract : The work reports a 3D gyroid acoustic crystal hosting multi‐fold degeneracies associated with topological surface states. The unique chiral morphology of the gyroid surface is leveraged to inherently provide this 3D acoustic material with non‐trivial dispersion topology, revealing the continuous design can ensure anomalous acoustic performance and remarkable functionalities without ad hoc designs.